The spatial distribution of blue carbon in the coastal wetlands of China. (30th June 2019) - Meng, Weiqing; Feagin, Rusty A.; Hu, Beibei; He, Mengxuan; Li, Hongyuan
Abstract: Coastal wetland losses in China are globally-relevant issues, as formerly sequestered soil organic carbon is released as CO2 into the atmosphere. Wetland losses also reduce the primary production by plants that would otherwise bury carbon in the future. More than 50% of these ecosystems have been lost globally over the last half century, with this number approaching 58% in China. The negotiation of international accords such as the Paris Climate Agreement rely on the accurate assessment of ecosystem-held carbon quantities. Our objective was to provide the first national scale survey of coastal wetland-based carbon in China. The average soil organic carbon stock (Mg SOC ha −1 ) across all three types of ecosystems was 236.91, with an average of 344.67 for mangroves, 175.14 for seagrass, and 134.37 for salt marshes. The SOC stock was greatest at 30–60 cm of depth in the case of mangroves, as opposed to 0–20 cm of depth for salt marshes. In terms of the carbon content of the standing aboveground and belowground biomass (Mg C ha −1 ), mangroves contained by far the most with an average of 253.98 and 83.96, respectively. Carbon burial rates, or the annual flux of SOC into the soil column (Mg C ha −1 yr −1 ), were 2.26 ± 0.39 for mangroves, 1.38 ± 0.38 for seagrass, and 2.18 ± 0.24 for salt marshes. Through our work, we found a total of 48.12–123.95 Tg of C in China's coastal wetlands (down to 1 m of soil column depth), with an annual burial of 0.84 Tg yr −1 . We estimate the average annual emissions of CO2 to be on the order of 6.83 Tg CO2 yr −1, due to ongoing and extensive wetland loss and conversion.